Zakat as an Instrument of Income Redistribution: an Analysis from the Perspective of Islamic Microeconomics - Rizki Mulia Nanda; Nurul Hikmah; Fathin Azzahra; Husnul Mirzal; Ismail Nura (Universitas Dehasen Bengkulu, 2026)
This article examines the role of zakat as an instrument of income redistribution through the lens of Islamic microeconomics. Drawing on 22 peer-reviewed articles published between 2015 and 2025, selected through a Systematic Literature Review (SLR) methodology, the study identifies three principal mechanisms through which zakat operates: first, it facilitates direct income transfers to mustahik, substantially enhancing their welfare in accordance with the principle of diminishing marginal utility; second, it corrects distributional failures that market mechanisms alone are unable to resolve; and third, it stimulates the purchasing power of lower-income groups, thereby generating a local economic multiplier effect. On the basis of these findings, this article contends that zakat ought to be recognized not merely as a philanthropic obligation, but as an integral component of a just and inclusive economic architecture. Realizing this potential in practice requires the reinforcement of institutional governance and the professional management of zakat collection and distribution.